A Fubini Theorem in Riesz spaces for the Kurzweil-Henstock Integral - A. Boccuto; D. Candeloro; A. R. Sambucini (Journal of Function Spaces and Applications)
A Fubini-type theorem is proved, for the Kurzweil-Henstock integral of Riesz-space-valued functions defined on (not necessarily bounded) subrectangles of the “extended” real plane.